Cell Cycle Biomarkers and Soluble Urokinase-Type Plasminogen Activator Receptor for the Prediction of Sepsis-Induced Acute Kidney Injury Requiring Renal Replacement Therapy: A Prospective, Exploratory Study. Issue 12 (December 2019) - Nusshag, Christian; Rupp, Christoph; Schmitt, Felix; Krautkrämer, Ellen; Speer, Claudius; Kälble, Florian; Tamulyte, Sandra; Bruckner, Thomas; Zeier, Martin; Reiser, Jochen; Weigand, Markus A.; Uhle, Florian; et al.
Abstract : Objectives: Sepsis-induced acute kidney injury is the dominant acute kidney injury etiology in critically ill patients and is often associated with a need for renal replacement therapy. The indication and timing of renal replacement therapy are controversially discussed. We hypothesized that the product of the G1 -cell cycle arrest biomarkers tissue inhibitor of metalloproteinase-2 and insulin-like growth factor-binding protein 7 ([TIMP-2] × [IGFBP7]), and the soluble urokinase-type plasminogen activator receptor are of diagnostic value for the prediction of septic acute kidney injury courses requiring renal replacement therapy. Design: In this prospective study, critically ill patients were enrolled immediately after the fulfillment of Sepsis-3 criteria. Urinary [TIMP-2] × [IGFBP7] levels over time and serum soluble urokinase-type plasminogen activator receptor levels once at inclusion were measured. The primary endpoint was the development of septic acute kidney injury with the need for renal replacement therapy. Area under the receiver operating characteristic curves, de Long's tests, and logistic regression models were calculated. Setting: Two ICUs at Heidelberg University Hospital between May 2017 and July 2018. Patients: One-hundred critically ill patients with positive Sepsis-3 criteria. Interventions: None. Measurement and Main Results: Nineteen patients required renal replacement therapy. Diagnostic performance of urinary [TIMP-2] × [IGFBP7] improved over time with the highest area under the receiver operating characteristic curve of 0.89 (95% CI, 0.80–0.98) 24 hours after study inclusion. Soluble urokinase-type plasminogen activator receptor levels at inclusion showed an area under the receiver operating characteristic curve of 0.83 (0.75–0.92). The best discrimination ability for the primary outcome measure was achieved for [TIMP-2] × [IGFBP7] at 24 hours after inclusion by applying a cutoff value of greater than or equal to 0.6 (ng/mL) 2 /1, 000 (sensitivity 90.9, specificity 67.1). Soluble urokinase-type plasminogen activator receptor performed best by using a cutoff value of greater than or equal to 8.53 ng/mL (sensitivity 84.2, specificity 82.7). A combination of newly tested biomarkers with cystatin C resulted in a significantly improved diagnostic accuracy. Cystatin C in combination with [TIMP-2] × [IGFBP7] 24 hours outperformed all standard renal parameters (area under the receiver operating characteristic curve 0.93 [0.86–1.00]). Conclusions: [TIMP-2] × [IGFBP7] and soluble urokinase-type plasminogen activator receptor are promising biomarker candidates for the risk stratification of septic acute kidney injury patients with the need for renal replacement therapy. Abstract : Supplemental Digital Content is available in the text.